Evaluasi Program Pemberian Makanan Tambahan pada Baduta yang Stunting di Wilayah Kerja Puskesmas Panambungan Makassar - Umi Kalsum; Ayu Syah Putri; Tri Rikhaniarti M (SENTRI: Jurnal Riset Ilmiah, 2024)
Stunting is a chronic nutritional problem that remains a challenge in health development in Indonesia because it impacts physical growth, cognitive development, and children's future productivity. One of the interventions carried out by the government to overcome stunting is through the Supplementary Feeding Program (PMT) for stunted toddlers. Evaluation of the program's implementation is needed to determine the extent to which the program has been implemented in accordance with the applicable objectives and guidelines. Objective: to determine the effect of the supplementary feeding program on the incidence of stunting in toddlers. Method: The research design used was a cross-sectional design. The population in this study were all stunted toddlers in the Panambungan Community Health Center working area for the period August - October 2024, a total of 68 toddlers, with a sample size of 36 toddlers, with a purposive sampling technique, data collection was carried out using a questionnaire, the collected data were then processed and analyzed using the Spearman test. Results: The study showed the results of the Spearman rho test with a p value of 0.003 (p value <0.05) so Ha was accepted, with a Correlation Coefficient value of 0.871 or 87.1%, the weight of the relationship was very close, which means there was an influence of the supplementary feeding program on the incidence of stunting in toddlers. Conclusion: The supplementary feeding program for toddlers was very closely related to the incidence of stunting in the working area of ​​the Panambungan Community Health Center, Makassar City.